The Public Health Approach to Campus Suicide Prevention. Issue 141 (22nd March 2013) - Jodoin, Elizabeth C.; Robertson, Jason
Abstract: This chapter explores public health theories and approaches to suicide prevention on campus. Implications for student affairs and higher education personnel regarding suicide prevention programming are discussed.